Eu não nasci de chocadeira: a polêmica entre reformistas e tradicionalistas sobre o estatuto das famílias do século XXI - Guedes, Tarcísio Pereira (2023)
The hegemonic discourse on the configuration of the Brazilian family is determined by the traditional parameters of Western civilization, materialized in the Federal Constitution of 1988: father, mother and children. A reformist counter-discourse, based on affectivity, requests the legal recognition of several family configurations already existing in our society, from the Law Project called Statute of Families of the XXI Century, motivation for a polemic event. From this, we are faced with the problem of which elements potentiate/accelerate the polemic event and verbal violence in the political space on the family issue and what are the possibilities of modulating management of the intensity of verbal violence. Under the theoretical framework of the Dialogical Analysis of Argumentation, an epistemological-methodological encounter between Bakhtin's dialogism and the New Rhetoric of Perelman and Olbrechts-Tyteca, we define the polemical event, the polemical acts, the micro-acts and the polemical alter ethos. Verbal violence is understood as the polemical act and the bivocal family sense dispute as the polemical micro-act. We have as a general objective to analyze the polemical event in question in order to understand the functioning of verbal violence and argumentation between the two antagonistic camps disputing the meaning of family in the political space, debated in an ordinary session of the Human Rights and Minorities Commission of the House of Representatives, on August 21, 2019, duly transcribed in official tachygraphic notes. The specific objectives are to discuss the pertinence of the dialogic analysis of argumentation and its polemical dialogism; to analyze the polemical event around the Statute of Families of the 21st Century and the constitution of the fields in conflict; to discuss verbal violence as a polemical act, seeking to understand in what way the management of the polemic can sharpen its intensity. Our results point to the polemic as a deep disagreement, intensified by the interincomprehension between the two fields, polarization and intensified by verbal violence. The latter is, in turn, difficult to be modulated as to the possibilities of its management in the public political space, demanding from the arguing dialogic subjects the responsible ethical exercise of their argumentative-enunciative acts, in that space.